Financial Planning for MSMEs: Improving Cash Flow Management and Saving Behavior Among Cafe Owners in Salatiga City - Arda Raditya Tantra; Bambang Ahmad Indarto; Fitri Dwi Jayanti (International Journal of Community Empowerment, 2026)
Financial planning literacy among micro, small, and medium enterprises (MSMEs) in Indonesia remains critically low, particularly among cafe owners who frequently conflate personal and business finances, operate without cash flow monitoring, and lack structured saving or investment habits. This community service study aims to improve financial planning understanding and practices among cafe owners in Salatiga City through structured education, practical workshops, and individualized mentoring. The program was conducted from March to May 2026, involving 50 cafe owners from the Salatiga Cafe and Coffee Shop Entrepreneurs Association. Results demonstrated a statistically significant increase in participants’ mean financial literacy score from 41.6 to 79.8 (on a 100-point scale), alongside a 78.2% improvement in participants’ financial planning behavior index. A total of 41 out of 50 participants successfully prepared a personal business cash flow projection and a three-month saving plan independently. These findings confirm that structured, practice-based financial education effectively promotes sustainable financial behavior among cafe operators and may serve as a replicable model for similar initiatives across Indonesian cities.